Standardization for 5G technology and beyond: impact on military communications - Miličević, Zoran M.; Bojković, Zoran S.; Bojković, Nataša S.; Živojinović, Tanja M. (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: The presented review paper deals with the standardization proces for 5G technology and beyond and its impact on military communications.Methods: Dominant methods such as analyzes and syntheses were provided for considering the key aspects of the 5G standardization evolution process through presentations of the roles of different Third Generation Partnership Project (3GPP) standard releases and its implementation and usage in military communication networks environment.Results: The background and key areas in 5G evolution and beyond are presented. Also, 5G standardization and military issues and challenges are discussed.Conclusion: Standardization for 5G and the emerging 6G landscape is extremely complex and highly innovative with many rapidly evolving industry-driven and societal requirements. Standard development organizations, industry, and academia need to collaborate on standardization to facilitate worldwide interoperability. The paper gives an overview of standardization functionalities and efforts to improve 5G system performance as well as its impact on military communications and services. It analyzes the areas of major enhancements for the existing features and expansion to new use cases and industries as well as to military usage through the 3GPP Releases, starting from Release 15 as 5G Basic, over 16 and 17 as 5G Evolution, up to 18 and 19 as 5G Advanced which precede the upcoming Release 20 and the initial 6G network whose launch is expected by the end of this decade.
Keywords: the fifth generation (5G) technology; 5G standardization process releases; 5G functionalities; 5G interoperability